Equal Protection, English Language Learners, and Desegregation (Study of Islamic Educational Leadership Management) - Agus Suryadi; Khairani Nasution; Muhammad Rifai Harahap; Mhd Syahdan Lubis; Amiruddin Siahaan; Inom Nasution (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
The difference principle is designed to be applied in a school community setting where the previous conditions have been met. Inequality may or may not be defined in terms of race, ethnicity, gender, or socioeconomic status. For example, a student may be advantaged in one area (musical talent, for example) and disadvantaged in another (mathematical talent, for example), with little association with gender or race. This paper wants to know how the form of freedom of expression of students. The first amendment rights of students limit the freedom of students, how is the role of educational institutions in managing the freedom of students. Freedom is situationally limited in religion, law, ethics, culture and morals. The Supreme Court seeks to enforce students' First Amendment rights while knowingly admitting that students don't have the same expressive rights inside the school building gates as they do outside the gates. Legal guidelines can be ambiguous, and finding the right balance between student rights, a positive school environment, and the obligations of order and discipline can be difficult. The interaction of the system world and the lifeworld determines the school's normative environment.